Pemberdayaan masyarakat melalui inovasi produk sari jeruk nipis LemooGi’ - Asysyuura; Suherman; Rasid, Muhammad; Khalik; Risdayanti; Ramadhani, Miranti Eka; Yusril. M, Muhammad; Putri A.P, Diadjeng; Fatmawaty, Sabinah; Ramadhan. R, Muhammad Suci; Heryansah, Dicky; Haris, Muh. (Jurnal Dedikasi Masyarakat, 2024)
Betao Village in Sidrap Regency is a key lime farming center facing challenges related to price fluctuations and the low market value of raw limes. To address this issue, the LemooGi’ product innovation program was introduced as a solution to process limes into ready-to-consume lime juice. This initiative involved academics from STIP Yapi Bone and Universitas Muhammadiyah Parepare, in collaboration with the Mekar Tani II Farmers Group as the primary partner. The implementation method included raw material preparation, hygienic production processes, sterilization, and product packaging. The program results indicate that LemooGi’ has a higher market value compared to fresh limes and contributes to increasing local farmers’ income through micro-enterprise development based on local commodities. Active participation from farmers and students in this program highlights the significant potential for further development. This innovation is expected to enhance farmers' economic well-being and expand the market for processed lime-based products.